Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Mixing overstory tree- and understory fern-derived dissolved organic carbon produces non-additive effects on biodegradation in subtropical forests of southern China - Su-Li Li; Zhi Zheng; Yi-Dong Ding; Jia-Wen Xu; Rong Mao (Plant and Soil, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Specific protein 1 inhibitor mithramycin A protects cardiomyocytes from myocardial infarction via interacting with PARP - Haihua Geng; Yamin Su; Rong Huang; Mengkang Fan; Xiaofei Li; Xiaochen Lu; Hongzhuan Sheng (In Vitro Cellular & Developmental Biology - Animal, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

The CMIP6 Historical Simulation Datasets Produced by the Climate System Model CAMS-CSM - Xinyao Rong; Jian Li; Haoming Chen; Jingzhi Su; Lijuan Hua; Zhengqiu Zhang; Yufei Xin (Advances in Atmospheric Sciences, 2021)
This paper describes the historical simulations produced by the Chinese Academy of Meteorological Sciences (CAMS) climate system model (CAMS-CSM), which are contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6). The model description, experiment design and model outputs are presented. Three members’ historical experiments are conducted by CAMS-CSM, with two members starting from different initial conditions, and one excluding the stratospheric aerosol to identify the effect of volcanic eruptions. The outputs of the historical experiments are also validated using observational data. It is found that the model can reproduce the climatological mean states and seasonal cycle of the major climate system quantities, including the surface air temperature, precipitation, and the equatorial thermocline. The long-term trend of air temperature and precipitation is also reasonably captured by CAMS-CSM. There are still some biases in the model that need further improvement. This paper can help the users to better understand the performance and the datasets of CAMS-CSM.